Cytokines in relation to hCG are significantly altered in asymptomatic women with miscarriage: a pilot study - Freis, Alexander; Schlegel, Janina; Daniel, Volker; Jauckus, Julia; Strowitzki, Thomas; Germeyer, Ariane (Reproductive biology and endocrinology, 2018)
Spontaneous abortion is one of the most common complications in early pregnancy. A preventive test to identify women who will experience a miscarriage, even before first symptoms occur, is not established. Activation of maternal immunological tolerance seems to be essential for early fetal development and various cytokines have been described in different stages of pregnancy. Therefore, we aimed to investigate if chemokine levels at the time of pregnancy testing relative to human Choriogonadotropin (hCG) are altered in patients who will experience a miscarriage in this pregnancy.
Gesehen am 08.10.2018